MiR-664 Protects Against UVB Radiation-Induced HaCaT Cell Damage via Downregulating ARMC8 - Chen Zhang; Xiongxiong Xie; Yawen Yuan; Yimeng Wang; Meijuan Zhou; Xiangzhi Li; Peilin Zhen (SAGE Publishing, 2020)
Background: MiR-664 has been demonstrated to play an important role in dermal diseases. However, the functions of miR-664 in ultraviolet B (UVB) radiation-induced keratinocytes damage remain to be elucidated. Objective: The present study aimed to investigate the molecular mechanisms under the UVB-induced keratinocytes damage and provide translational insights for future therapeutics and UVB protection. Methods: HaCaT cells were transfected with miR-664, either alone or combined with UVB irradiation. Levels of messenger RNA and protein were tested by quantitative real-time polymerase chain reaction and Western blot analyses. Cell proliferation, percentage of apoptotic cells, and expression levels of apoptosis-related factors were measured by Cell Counting Kit-8 assay, flow cytometry assay, and Western blot analysis, respectively. Results: We found that a significant increase in miR-664 was observed in UVB-induced HaCaT cells. Overexpressed miR-664 promoted cell vitalities and suppressed apoptosis of UVB-induced HaCaT cells. Additionally, the loss/gain of armadillo-repeat-containing protein 8 (ARMC8) rescued/blocked the effects of miR-664 on the proliferation of UVB-induced HaCaT cells. Conclusions: Our data demonstrate that miR-664 functions as a protective regulator in UVB-induced HaCaT cells via regulating ARMC8.